The role of the mTOR pathway in diabetic retinopathy - Casciano, Fabio; Zauli, Enrico; Rimondi, Erika; Mura, Marco; Previati, Maurizio; Busin, Massimo; Zauli, Giorgio (Frontiers in Medicine, 2022)
The retina is the part of the eye that translates light signal into an electric current so that it can be sent to the brain as visual information. To do that, the retina requires fine-tuned vascularization for its energy supply. Diabetic retinopathy leads to changes to the eye vascularization that reduce the oxygen supply with concurrent retinal neurodegeneration. During this process, the mTOR pathway seems to coordinate retinal neurodegeneration with multiple anabolic and catabolic processes closely related to chronic hyperglycemia, such as autophagy, oxidative stress, cell death and pro-inflammatory cytokine release. In this review, we give an overview of the normal anatomy of the retina and how hyperglycemia’s overactivating or inhibiting the mTOR pathway can be involved in the neurodegeneration underlying this disease.